Pulmonary hypertension in the primary care setting. Issue 11 (21st November 2022) - Lua, Stephanie; Church, Colin
Abstract : Pulmonary hypertension can be very difficult to identify and patients often experience a long delay before diagnosis. This article aims to raise awareness of pulmonary hypertension in the primary care setting, and discusses the role of the GP in diagnosis and management, with a focus on pulmonary arterial hypertension.